ISOLASI Escherichia coli PADA DAGING SAPI SEGAR YANG DIPEROLEH DARI BEBERAPA PASAR TRADISIONAL DI PEKANBARU - Elsie, -; Harahap, Israwati (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Escherichia coli is a bacteria that inhabitant in the cattle or human intestine. Raw beef sold in the traditional markets is easily to contaminated by E. coli. Itâs because the markets is one of the vulnerable and the risk is high enough against contamination. The goal of this research is to detect E. coli contamination in the fresh raw beef at several markets in Pekanbaru. This research used 100 gr fresh raw beef purchased from the six traditional markets in Pekanbaru. The study begins with a Most probable Number (MPN) test, than isolation and identification of the media ECB and L-EMB, initially with IMViC test (Indol, Methyl Red, Voges Praskauer and Citrate). Results of MPN test showed that all raw beef were contaminated E.coli with MPN varying value.